If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x * 3 + -8 + 2x + -4 = 2 + 3x * 6 Reorder the terms for easier multiplication: 5 * 3x + -8 + 2x + -4 = 2 + 3x * 6 Multiply 5 * 3 15x + -8 + 2x + -4 = 2 + 3x * 6 Reorder the terms: -8 + -4 + 15x + 2x = 2 + 3x * 6 Combine like terms: -8 + -4 = -12 -12 + 15x + 2x = 2 + 3x * 6 Combine like terms: 15x + 2x = 17x -12 + 17x = 2 + 3x * 6 Reorder the terms for easier multiplication: -12 + 17x = 2 + 3 * 6x Multiply 3 * 6 -12 + 17x = 2 + 18x Solving -12 + 17x = 2 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -12 + 17x + -18x = 2 + 18x + -18x Combine like terms: 17x + -18x = -1x -12 + -1x = 2 + 18x + -18x Combine like terms: 18x + -18x = 0 -12 + -1x = 2 + 0 -12 + -1x = 2 Add '12' to each side of the equation. -12 + 12 + -1x = 2 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 2 + 12 -1x = 2 + 12 Combine like terms: 2 + 12 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| 120/10=-3y | | -12=-2.5x-3 | | 4-x+8=6 | | 2x+2x+3=-7 | | 0.5x+0.16=0.75 | | 6k^2-53k-9=0 | | 4x*6=8x-1 | | 4(x+9)=-24 | | 0.5x+6=0.75 | | -30=9/-5 | | 2-2n=3n+10 | | 4d-3=d+42 | | 5(N+1)=-2n+4(n-4) | | X-7+20=7x-10 | | -2/5÷-2/3 | | (3z+7)(3z+7)= | | 3x=.5(5x+12) | | y+5=-5x | | x^2+31=24 | | D+(1.1+-5d)=4.8 | | 12(5-x)=8 | | (2m-3)=20-4m | | 6(b-5)=18-2b | | 18a+3=3-18a | | 3m-n=-2n | | 5x+17=4x-29 | | -3(c-4)=9 | | 2x8-20/4-8= | | 2x+15=8x-45 | | -16x^2+55x=26 | | 2=20-2(q+P) | | (25+2x)(20+2x)=0 |